LANGUAGE INTERFERENCE OF SOCIAL MEDIA APPLICATIONS ON MOTHER LANGUAGE IN SOUTH SULAWESI - Saleh, Firman -; Yusuf, Rudy; Radhiyani, Fitri (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2025)
The development of digital technology, especially social media applications, has brought significant changes in language use. One of the linguistic phenomena that has emerged is diction interference, which is the mixing of vocabulary from the language used in social media applications into the speaker's mother tongue. This study aims to identify the forms of diction interference that occur in everyday communication, analyze the factors that cause it, and examine its impact on the sustainability of the mother tongue. The method used in this study is descriptive qualitative with data collection techniques through observation, interviews, and document analysis. The results of the survey show that diction interference occurs in various forms, such as direct adoption of foreign vocabulary, changes in meaning, and mixing of grammatical structures influenced by the language in social media applications. The main factors causing this phenomenon include the intensity of social media use, the dominance of global languages ​​in the digital world, and perceptions of modernity and practicality in communication. The impacts include changes in language patterns in everyday conversation, strengthening diglossia, and the potential for weakening the ability to speak the mother tongue purely. This study emphasizes that although diction interference is part of linguistic dynamics, efforts to preserve the mother tongue still need to be made to maintain the balance between language adaptation and cultural identity.